A Geospatial Approach for the Assessment and Management Prioritization of Philippine Terrestrial Key Biodiversity Areas: Towards Meeting Global Sustainability Targets - M. A. Cruz (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Biodiversity plays a major role in sustaining life on Earth, with innumerable benefits to society. However, biodiversity loss and extinction due to external threats have been increasing globally. Key biodiversity areas (KBAs), although without an established legal basis, are important sites that contribute to the persistence of biodiversity. The use of geospatial technology has been proven to be a reliable, cost-effective, and targeted approach for biodiversity conservation and ecological management. In this study, data integration and spatial analysis were used in developing an easily interpretable and adaptable quantitative assessment and prioritization of KBAs. The identification of priority KBAs was based on threatened species, human-made structures, forest fragmentation, and forest loss. The integrated rankings revealed that Sibutu and Tumindao, Ragay Gulf, and Simunul and Manuk Manka Islands were the three highest priority KBAs based on the integrated factor scores, with all having almost zero overlap with protected areas (PAs). Among the top twenty KBAs, twelve sites had less than 2% overlap with PAs. Priority KBAs were identified in this study, either by means of the integrated rankings or by analyzing the relationships of the factor values. Implementing a management system in these identified priority KBAs, either as PAs or other effective conservation measures (OECMs) will lead to improving the condition in these sites. Moreover, these additional areas for conservation can contribute towards SDG 15 and in meeting the Philippines’ commitment to the “30 by 30” target under the Kunming-Montreal Global Biodiversity Framework.